3(8-3(1))=5(2+1)

Simple and best practice solution for 3(8-3(1))=5(2+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(8-3(1))=5(2+1) equation:


Simplifying
3(8 + -3(1)) = 5(2 + 1)

Multiply -3 * 1
3(8 + -3) = 5(2 + 1)

Combine like terms: 8 + -3 = 5
3(5) = 5(2 + 1)

Multiply 3 * 5
15 = 5(2 + 1)

Combine like terms: 2 + 1 = 3
15 = 5(3)

Multiply 5 * 3
15 = 15

Add '-15' to each side of the equation.
15 + -15 = 15 + -15

Combine like terms: 15 + -15 = 0
0 = 15 + -15

Combine like terms: 15 + -15 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 7z=180-22 | | (8-3(1))=5(2+1) | | 27x^3-1= | | 9x^2-28x+3=0 | | -3p+7=6-10p-5 | | 9x+7=3x-9 | | 2r-6r=12 | | -(c-12c-c-3c)= | | 4(b+3)=24 | | -18-6k=6(p-8) | | x(3x+11)=20 | | 12+z-x= | | 6m^3n^3*8m^2n^3= | | 4b+2=6b-6 | | (8-3(1))= | | 2X+8+3X= | | -56=4-5x | | 7(x-2)+2(x+4)+27=180 | | -14b+28=-10b+30 | | 13m=11 | | 6x+5=-7+4x+24 | | 6x^4=5 | | x.x-x=2x-2 | | 1+4n+1=-18 | | 7x^4+9x^3-41x^2-13x+6=0 | | x^2=-8+6x | | 8-5(x+1)=9+x | | 6(2x+4)=4(3x+6) | | 14-(2q+5)=-29+9 | | 72=-12m | | 12a^5-6a^2= | | 2(x+3)+4x-3=5x+12 |

Equations solver categories